Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content: 1. The effectiveness of a program based on active learning in developing creative thinking skills among students of the Islamic Studies Curriculum Department at the College of Education, Arhab Ms. Samia Ali Ahmed Al-Harazi, Prof. Ahmed Hassan Ghalib, Prof. Hamid Farhan Al-Afif 2. The Awareness of Faculty Members and Those in Authority at King Saud University Regarding the Importance of Reputation Management and Its Impact on Educational Institutions Mrs. Maha Naif Alotibi, Dr. Saud G. Albeshir 3. Organizational culture in school administration in girls’ schools, Asir Education, during the Corona pandemic Ms. Norah Khaloofah Hamed 4. The Extent of Virtual Reality’s Impact on Computer Learning Motivation: A Comprehensive Review of Literature and Educational Research Ms. Amirah Mohammed Albalawi 5. The level of psychological stress and its relationship to some variables among female students of the Faculty of Education at the University of Hail Mrs. Alaa Falah Al-Hamdhawi 6. Psychological Hardiness and its relationship to psychological security among female’s students at the University of Hail Mrs. Sarah Salman Alslemi 7. Differences in Emoji Usages Based on Self-Presentation Strategies and Motivations on Social Media and Their Role in Persuasive Messages Ms. Lina Fawaz Alnasrallah, Dr. Heyla Abdullah Alselim 8. The degree of awareness of female students exposed to electronic blackmail in the basic stage of the concepts of moral intelligence and its relationship to the level of blackmail Ms. Reema Awwad Alsmeheen, Dr. Anas Saleh Aldalaien